Primary Malignant Melanoma of Uterine Cervix - Shrestha, Ramesh; Adhikari, Purbesh; Rimal, Surya Prasad; Basnet, Pritha; Rijal, Pappu; Regmi, Mohan C. (Nepal Journal of Obstetrics and Gynaecology, 2020)
Primary malignant melanoma of cervix (PMMC) is rare and aggressive cancer of uterine cervix. It presented as vaginal discharge, post coital bleding and blackish cervical growth that was biopsied and radical hysterectomy performed immediately after getting the histopathological diagnosis at stage-1B2 (FIGO staging, 2018). Post-treatment, she was recurrence free at nine months of regular follow up visit. Keywords: cervix, malignant, melanoma, primary